Attenuation of Strychnine-Induced Epilepsy Employing Amaranthus viridis L. Leaves Extract in Experimental Rats. (14th March 2023) - Bharadwaj, Aashish; Sharma, Ashwani; Singh, Talever; Pathak, Devender; Virmani, Tarun; Kumar, Girish; Sharma, Anjali; Alhalmi, Abdulsalam
Abstract : Objective . Epilepsy is one of the most prevalent neurological illnesses defined by periodic seizures with or without loss of consciousness caused by aberrant neural activity. There are many allopathic medications available for the treatment of epilepsy such as phenytoin (PHY), but the side effects are a major concern. Therefore, the present study involved the evaluation of the pharmacological significance of Amaranthus viridis L. extract (EAV) in the management of strychnine (STR)-induced epilepsy. Method . STR (3.5 mg/kg, i.p.) was injected into male rats 30 minutes after the pre-treatment of a standard drug (PHY: 20 mg/kg) and the two doses of EAV (EAV-200 and EAV-400 mg/kg, p.o.) to the respective groups to cause the convulsions. The anti-convulsant effect of EAV-200 and EAV-400 against STR-induced convulsion in rats was investigated in terms of convulsion onset, duration of convulsions, number of convulsions, and convulsion score. Furthermore, the mitochondrial function and integrity in the brain's prefrontal cortex (PFC) were also estimated. Results . EAV-400 significantly increased the onset of convulsion from 61.67 ± 3.051 to 119.2 ± 2.738 and reduced the STR-induced duration of convulsions from 144.8 ± 3.582 to 69.17 ± 3.736, number of convulsions from 4.000 ± 0.1592 to 1.533 ± 0.1542, and convulsion score from 5.000 ± 0.3651 to 2.833 ± 0.3073 in rats. EAV-400 significantly attenuated the STR-induced decrease in the mitochondrial function and integrity of the rat PFC. In rats, EAV-400 significantly accelerated the onset of convulsions while decreasing the STR-induced duration, frequency, and score. Conclusion . Based on investigational findings, EAV-400 could be inferred to be a possible anti-epileptic option for the treatment of epilepsy of this plan in preclinical research.